Combating Islamophobia in the Digital Sphere: An Analysis of Onepath Networks’ Communication Strategies - Layli Nurul Islamiyah; Lulur Rochmawati; Salsabila Laili Ramadhanti (Academia Open, 2025)
General Background: Islamophobia has intensified in the digital era as social media accelerates the spread of negative narratives about Islam and Muslims. Specific Background: In response, Onepath Networks—an Australian-based Islamic media organization—actively counters misinformation through targeted digital communication strategies. Knowledge Gap: Existing studies rarely provide a focused examination of how a single Islamic media institution systematically constructs counter-narratives across social platforms. Aims: This study analyzes Onepath Networks’ use of educational, humanistic, and phenomenological content on YouTube and Instagram to combat Islamophobia. Results: The findings indicate that storytelling techniques, personal narratives, and peace-oriented messaging effectively reduce bias by humanizing Muslim identities and fostering intercultural understanding. Novelty: This research offers a case-specific analysis that demonstrates how a faith-driven digital media organization operationalizes counter-Islamophobia strategies beyond general social media activism. Implications: The study highlights the potential of well-designed digital communication strategies to dismantle stereotypes, strengthen inclusive discourse, and guide future media-based efforts against Islamophobia. Highlights: Analyzes Onepath Networks’ strategic use of YouTube and Instagram to counter Islamophobia. Highlights phenomenological storytelling and personal narratives to humanize Muslim identities. Shows how structured digital communication can reshape public perceptions and foster intercultural understanding. Keywords: Islamophobia, Social Media, Onepath Networks, Communication Strategies, Digital Counter-Narratives